2014
DOI: 10.1080/1357650x.2014.920339
|View full text |Cite
|
Sign up to set email alerts
|

Laterality of foetal self-touch in relation to maternal stress

Abstract: This longitudinal observational study investigated whether foetuses change their hand preference with gestational age, and also examined the effects of maternal stress on lateralized foetal self-touch. Following ethical approval, fifteen healthy foetuses (eight girls and seven boys) were scanned four times from 24 to 36 weeks gestation. Self-touch behaviours which resulted in a touch of the foetal face/head were coded in 60 scans for 10 min and analysed in terms of frequency of the foetuses using left and righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 22 publications
0
21
1
2
Order By: Relevance
“…The authors concluded that visual availability interferes with hand choice. Other factors, such as maternal stress (Reissland et al, 2014), are mentioned. Preslar et al (2014) also found no relationship between gender and handedness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that visual availability interferes with hand choice. Other factors, such as maternal stress (Reissland et al, 2014), are mentioned. Preslar et al (2014) also found no relationship between gender and handedness.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, genetic factors predominate, but environmental factors such as greater movement of non-dominant limb can lead to reduced asymmetry (McCartney & Hepper, 1999;Teixeira & Paroli, 2000). Recently, Reissland, Aydin, Francis, and Exley (2014) showed that maternal stress between the 24 th and 36 th week induces increased fetal self-touching with the left limb. Thus, the process of brain lateralization could be influenced by the biochemical imbalance that maternal stress causes in the uterus.…”
mentioning
confidence: 99%
“…For example, the fetuses of mothers reporting stress have been found to show more left handed touches. 53 This adds further weight to the claim that ultrasound images of the fetus can give an insight into development in utero.…”
Section: Use Of Ultrasound Images Can We Use Fetal Facial Movements Fmentioning
confidence: 99%
“…53 Reissland et al 54 examined the effects of maternal stress on lateralized fetal self-touch to the face/head using 4-D ultrasound. The maternally reported stress level was significantly positively correlated with fetal left-handed self-touches.…”
Section: Maternal and Fetal Stressmentioning
confidence: 99%